Risk Factors Associated with Hypertensive Disorders in Pregnancy - Bushra Khan, Sadia Bashir, Ayesha Khan Khakwani, Sajilah Karim, Zia Ul Islam, Atqa Firdous, MM Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: To determine the risk factors of hypertensive disorders of pregnancy (HDP) among pregnant women. Methods: In this study, we included 200 patients, 100 were those who were diagnosed with any HDP and 100 were control patients, who were pregnant and did not have any HDP. The study was conducted in Nishtar Hospital Multan from June-2021 to June-2022. Women having blood pressure (BP) ≥140/90 mmHg was 20 weeks of gestation were labelled as having HDP. Risk factors of HDP were noted. Results: Mean age of patients was 28.45±8.45 years in cases and 30.41±9.61 years in controls. On univariate analysis, age >35 years Univariate analysis was done to determine the risk factors of HDP. Age >35 years (OR 3.63 (1.08-12.18), p-value 0.02), obesity (OR 3.16 (1.03-9.68), p-value 0.03), living in rural area (OR 2.26 (1.01-5.05), p-value of 0.04), nulliparity (OR 3.45 (1.22-9.75), p-value 0.016), positive family history of hypertension (OR 4.04 (1.21-13.43), p-value 0.017), twin pregnancy, lack of regular visit of antenatal clinics (OR 0.31 (0.12-0.95), p-value 0.02), Previous history of abortion (OR 9.33 (1.12-77.7), p-value 0.01), chronic hypertension (OR 4.5 (0.91-22.7), p-value 0.04). Conclusion: This study revealed rural lifestyle, old age, multiple pregnancy, and pre-pregnancy weight as independent risk factors. It is advised that health care providers employ these indicators as a screening tool for the prediction, early diagnosis, and timely intervention of pregnant hypertensive problems. Keywords: Gestational hypertension, Preeclampsia, Hypertensive disorders of pregnancy.